Identification of the Damage Scenarios under Cyclic Loading of a Coated 300M Steel by Infrared Thermography Measurements - Pierrick Lepitre; Sylvain Calloch; Matthieu Dhondt; Martin Surand; Cédric Doudard (Physical Sciences Forum, 2022)
An ultra-high-strength steel used in aeronautics for landing gears, 300M is generally shot-peened and coated with high-velocity oxygen fuel-sprayed WC-10Co-4Cr to improve its tribological behavior. In the literature, few treatment parameters have been tested to analyze the impacts on fatigue properties. Post-mortem optical microscopy has shown that the coating–substrate interface plays a key role in fatigue life, with new fracture scenarios having been observed compared to uncoated steel. To explore damage scenarios, infrared thermography measurements provide substantial information complementary to optical microscopy. The identification of damage scenarios is the first step in developing a lifespan forecast model.